Improvement of Flow Properties of Highly Waxy Crude Oil with the application of SiO2 and Graphene Oxide nanoparticles aided by Light Crude Oil - Khaklari, Gaurav Himanta; Talukdar, Prasenjit (International Journal of Experimental Research and Review, 2024)
The rheological behaviour of crude oil mixtures comprising both heavy and light components along with chemical additives is of significant interest due to its relevance in the petroleum industry. Understanding the flow properties of these mixtures is crucial for efficient transportation, processing, and refining operations. This study investigates the effectiveness of incorporating light crude oil and nanoparticles as additives to mitigate wax-related flow issues. The test involves six different waxy/heavy and light crude oil mixture concentrations along with Graphene Oxide and Silicon Dioxide nanoparticles. Rheological tests were conducted to evaluate the impact of these additives on the flow behaviour of waxy crude oil. The rheological characterization involved measuring the viscosity, yield stress, and shear rate dependencies of waxy crude oil samples with varying concentrations of light crude oil and nanoparticles. Nano-materials have emerged as promising candidates for mitigating wax deposition issues and enhancing the fluidity of crude oil. Nevertheless, the intricate nature of crude oil has made it challenging to elucidate the underlying mechanisms governing wax resolution, crystal modification, and flow improvement. The results revealed notable improvements in the rheological properties of the treated crude oil, including reduced viscosity and enhanced flowability, even at low temperatures. The incorporation of light crude oil and nanoparticles proved to be a promising strategy for modifying the rheological behaviour of waxy crude oil, ensuring improved flow assurance. This study contributes to understanding innovative approaches to address flow challenges in waxy crude oil systems, thereby offering potential solutions for the oil and gas industry.